Reorientasi Efektivitas Nilai Standar Kelulusan Bagi Siswa dalam Upaya Mencetak Generasi yang Berkualitas di Bidang IPTEK dan IMTAK - M. Huda A.Y. (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The implementation of the standard of passing grades has so far been still ineffective in preparing the next generation who is qualified scientifically and religiously as has been outlined in the objective of the national education. As a result, some factors especially which have social, economic, cultural, knowledge, and political implementations need to be reformed and reoriented so that there are stronger relations between education and social values in real life contexts.